New replacement name for the planthopper genus Potiguara Hoch et Ferreira, 2013 (Hemiptera: Fulgoromorpha: Kinnaridae) - Xing, Ji-Chun; Hoch, Hannelore; Chen, Xiang-Sheng (Zootaxa, 2013)
The Kinnaridae genus Potiguara was established by Hoch & Ferreira (2013) with the type species Potiguara troglobia Hoch et Ferreira, 2013 from Brazil. So far, this genus includes only the type species. Nevertheless, the name Potiguara is preoccupied and it was initially introduced by Machado et Brito, 2006 for an extinct genus of the fish family Pycnodontidae (with the type species Coelodus rosadoi Silva Santos, 1963 from Brazil). Thus, the genus Potiguara Hoch et Ferreira, 2013 is a junior homonym of the genus Potiguara Machado et Brito, 2006. According to Article 60 of the International Code of Zoological Nomenclature, we propose the new replacement name Kinnapotiguara nom. nov. for Potiguara Hoch et Ferreira, 2013. Accordingly, a new combination is herein proposed for the kinnarid planthopper species currently included in this genus: Kinnapotiguara troglobia (Hoch et Ferreira, 2013) comb. nov.